Evaluation of Megasphaera elsdenii supplementation on rumen fermentation, production performance, carcass traits and health of ruminants: a meta-analysis - Irwan Susanto; Komang G. Wiryawan; Sri Suharti; Yuli Retnani; Rika Zahera; Anuraga Jayanegara (Animal Bioscience, 2023)
Objective This study was conducted to evaluate the use of Megasphaera elsdenii (M. elsdenii) as a probiotic on rumen fermentation, production performance, carcass traits and health of ruminants by integrating data from various related studies using meta-analysis. Methods A total of 32 studies (consisted of 136 data points) were obtained and integrated into a database. The parameters integrated were fermentation products, rumen microbes, production performance, carcass quality, animal health, blood and urine metabolites. Statistical analysis of the compiled database used a mixed model methodology. Different studies were considered random effects, while M. elsdenii supplementation doses were considered fixed effects. p-values and the Akaike information criterion were employed as model statistics. The model was deemed significant at p<0.05 or had a tendency to be significant when p-value between 0.05<p<0.10. Results Supplementation with M. elsdenii increased (p<0.05) some proportion of fermented rumen products such as propionate, butyrate, isobutyrate, and valerate, and significantly reduced (p<0.05) lactic acid concentration, acetate proportion, total bacterial population and methane emission. Furthermore, the probiotic supplementation enhanced (p<0.05) livestock production performance, especially in the average daily gain and body condition score. Regarding the carcass quality, hot carcass weight and carcass gain were elevated (p< 0.05) due to the M. elsdenii supplementation. Animal health also showed improvement as indicated by the lower (p<0.05) diarrhoea and bloat incidences as well as the liver abscess. However, M. elsdenii supplementation had negligible effects on blood and urine metabolites of ruminants. Conclusion Supplementation of M. elsdenii is capable of decreasing ruminal lactic acid concentration, enhancing rumen health, elevating some favourable rumen fermentation products, and in turn, increasing production performance of ruminants.